Tanam Paksa di Keresidenan Tegal: Kajian Tentang Sistem, Pelaksanaan dan Dampaknya (1830–1870) - Hanafi, Setia; Nawiyanto, S. (Historia, 2022)
This article discusses the cultivation system applied in the Tegal Residency starting from the system, its implementation and the impact that arose on the community in that period. Cultivation system, which was implemented from 1830 to 1870, has become an important momentum for the socio-economic changes of the people in the Tegal Residency. The research problems to be dealt with here include an overview of the conditions Tegal Residency before the cultivation system, the implementation of cultivation system the residency, and the impact of cultivation system. The research method used is the historical method which consists of heuristics, source criticism, interpretation, and historiography. This study employs an economic sociology approach. The research results indicate that plantation activities already existed but have not developed well. The application of cultivation system encouraged plantations to expand by utilizing available resources, namely land and labor, both of which are closely related in traditional ties. Productivity levels increased for both sugar, coffee, indigo and tea plantations from before the implementation of cultivation system, although indigo and tea developed more slowly. This had an impact on society with the emergence of wage labor, population growth, benefits for colonial officials, and peasant resistance movements.